Introdução à estrutura matemática da mecânica quântica - Silva, Marcos Vinícius Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
It is common to see the lack of concern in the rigor of mathematics on the part of the physicists, specially in dealling whith quantum mechanics, but this can lead to inconsistency whitin the theory. In this work we explore part of this mathematical universe and then relate it to physics, evincing the importance of the mathematical formalism in physics and also discussing some speciﬁc cases in quantum mechanics

É comum ver a falta de preocupação no rigor da matemática por parte dos físicos, especialmente no trato da Mecânica Quântica, mas isso pode levar a inconsistências na teoria. Neste trabalho vamos explorarpartedesseuniversomatemáticoedepoisorelacionaremoscomafísica,mostrandoaoleitora importânciadoformalismomatemáticonafísicaalémdediscutiralgunscasosespecíﬁcosemmecânica quântica
Keywords: Teoria quântica; Fisica matematica; Hilbert, Espaço de; Topologia; Quantum theory